Política de educação integral no Estado do Pará: aspectos de sua implementação na rede estadual de ensino - Silva, Sandra Suely Lopes Souto da (2019)
This study intended to understand how the Integral Education Politic was implemented in a public school of State of Pará based on perceptions of the school board, management team and teachers. Therefore, studies in integral education from authors such as Cavaliere (2002), Moll (2009), Coelho (2009) in addition to studies on public policy implementation from authors such as Parente (2016) and Lotta (2014)were adopted as theoretical refence. The qualitative research took place through bibliographic research, document analysis and interviews with technicians from Secretaria de Estado da Educação and with school’s management and teachers. The following actors were interviewed: educational coordinator from the SEDUC headquarters, manager of the SEDUC unit at the school, school’s principal, coordinator and 9 teachers, in a total of 13 professionals. To analyze the data it was adopted the “content analysis” technique (BARDIN, 1977). Previous categories were elaborated according to the studied literature: adherence to the integral education policy and its challenges; how the implementation agents understand and perceive the proposal; qualification and training of the people involved in integral time school; structural conditions of the integral education policy; implementation agents’ discretion and interaction. The study concluded that adherence to the program was not total, there was resistance from some teachers related to pre-existing beliefs about school’s organization form and to the most effective teaching way in the classroom. The main challenge pointed out by the interviewees refers to the need of regular training by the central agency, as well as the adequacy of school’s spaces to attend integral education. The collected data indicates that the micro level agents seek to respond autonomously and using discretion to the challenges of infrastructure in the everyday school environment, including the lack of more effective support from SEDUC. It was possible to verify the engagement and cooperation of the interviewed professionals in the search for ways to overcome the hardships.